An Empirical Study on Settlement Pattern and Architectural Features of Rural Housing in Haor-basin Region of Bangladesh - Das, Subrata; Rahman, Md Arifur (Journal of Architectural/Planning Research and Studies (JARS), 2025)
The Haor region is dominated by annual flooding, and over 90% of the land is submerged underwater for half of the year. The compact rural settlements are surrounded by a vast scale of seasonal wetlands needed to sustain the challenging environment. The indigenous architecture and settlement technique ensure the small island-like village can cope with the climatic challenge while ensuring community social coherence. The concept of shared spaces, a sense of ownership and privacy without creating physical barriers and strictly following the orientation of the houses created unique features of the rural settlements in the Haor Basin area. However, the recent developments using non-local materials, resisting the natural force instead of coping with it, and breaking social coherence by destroying the continuity of spaces are creating adverse effects. Since the rural settlements have gone through organic development yet maintained the pattern through respecting indigenous knowledge, there needs to be formal documentation of the planning concepts. This research attempts to identify the settlement pattern from empirical study, on-site observation and analysis of the pattern with an understanding of local norms and architectural knowledge. It is evident from the study that the rural houses are built aligned with the cardinal directions even when the site orientation is different. The settlement clusters are linearly aligned to the monsoon flood flow direction. Though the linear courtyards are subdivided in terms of ownership, practically, they are maintained as barrier-free connectivity among houses within the same housing cluster.